For this case we have:
If after 2 hours the marathon runner has traveled 22 kilometers we have:
2h -----------> 22km
Applying a rule of three, we can know the time it takes to run 42km. So, we have:
2h -----------> 22km
x -------------> 42km
Where "x" is the time it takes to travel 42km. Resolving we have:
[tex]x = \frac {(42 * 2)} {22}[/tex]
[tex]x = \frac {84} {22}[/tex]
[tex]x = \frac {42} {11}[/tex]
[tex]x = 3.82 hours[/tex]
Thus, after 3.82 hours the marathon runner will travel 42km.
Answer:
3.82 hours